2020
DOI: 10.2217/fon-2019-0509
|View full text |Cite
|
Sign up to set email alerts
|

Enzalutamide plus androgen-deprivation therapy in hormone-sensitive prostate cancer: new perspectives from a current Phase III clinical trial

Abstract: Prostate cancer is a major health issue with an incidence of 1,100,000 worldwide. Eventually, 20–40% of curatively treated patients will face a biochemical recurrence. Lately, the treatment options in metastasized hormone sensitive prostate cancer (mHSPC) were rapidly evolving after years of stagnation. Encouraging results in clinical trials of combination treatment of androgen deprivation therapy with either chemotherapy or second-generation hormonal treatment indicate a paradigm shift in this clinical scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Recently, a combination treatment of enzalutamide and ADT for metastatic hormone-sensitive PCa (mHSPC) in phase III clinical trial has been reported. These reports concluded that enzalutamide offers a benefit in treatment post-docetaxel in mHSPC [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a combination treatment of enzalutamide and ADT for metastatic hormone-sensitive PCa (mHSPC) in phase III clinical trial has been reported. These reports concluded that enzalutamide offers a benefit in treatment post-docetaxel in mHSPC [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%